FPGAs : instant access - Maxfield, Clive, 1957- (Newnes instant access series., 2008)
FPGAs are central to electronic design! The engineers designing these devices are in need of essential information at a moment's notice. The Instant Access Series provides all the critical content that a computer design engineer needs in his or her daily work. This book provides an introduction to FPGAs as well as succinct overviews of fundamental concepts and basic programming. FPGAs are a customizable chip flexible enough to be deployed in a wide range of products and applications. There are several basic design flows detailed including ones based in C/C++, DSP, and HDL. This book is filled with images, figures, tables, and easy to find tips and tricks for the engineer that needs material fast to complete projects to deadline. *Tips and tricks feature that will help engineers get info fast and move on to the next issue *Easily searchable content complete with tabs, chapter table of contents, bulleted lists, and boxed features *Just the essentials, no need to page through material not needed for the current project.